An attempt to use pencil leads as cheap materials for electrochemical sensor. Issue 6 (21st December 2018) - Dang, Vu Hai; Anh, Nguyen Hoang; Yen, Pham Thi Hai; Giao, Nguyen Quynh; Ha, Vu Thi Thu
Abstract: Due to their electrochemical and economical characteristics, pencil leads can be used as electrodes for electrochemical analysis. These graphite‐based electrodes are recognized by their low‐cost and commercial availability. This paper presents the synthesis of gold nanodendrite network porous structure on pencil lead and its application in recording signals of Hg(II) in water environment. Influences of deposition time (tdep ) used to fabricate Au nanodendrite structure on electrodes surface, sensor electrochemical behaviors and voltammetric signal of Hg(II) have been studied. The obtained results open a possibility to employ this simple, eco‐friendly material in developing electrochemical sensor, which can be implemented for heavy metal detection.